2019
DOI: 10.1055/a-0869-7619
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between endoscopic mucosal healing and histologic inflammation during remission maintenance phase in ulcerative colitis: a retrospective study

Abstract: Background and study aims Recently, histological inflammation has been suggested to be an important predictor of sustained remission or relapse of ulcerative colitis (UC). In this study, we retrospectively compared severity of histological inflammation with endoscopic findings in UC patients with mucosal healing (MH) in the remission maintenance phase, and investigated whether histological healing could be a predictor of sustained remission. Patients and methods This study included 166 patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…We found that beyond degree of endoscopic healing, no conventional demographic or clinical factors could identify which patients treated‐to‐target of EH would achieve histologic remission. While prior studies have not evaluated factors associated with achieving histologic remission, they have not identified any systematic differences in patients who achieve histologic remission vs persistent histologic activity after achieving EH 2,3,5 . We show in this cohort that conventional baseline factors do not determine if patients are able to achieve histologic remission.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…We found that beyond degree of endoscopic healing, no conventional demographic or clinical factors could identify which patients treated‐to‐target of EH would achieve histologic remission. While prior studies have not evaluated factors associated with achieving histologic remission, they have not identified any systematic differences in patients who achieve histologic remission vs persistent histologic activity after achieving EH 2,3,5 . We show in this cohort that conventional baseline factors do not determine if patients are able to achieve histologic remission.…”
Section: Discussionmentioning
confidence: 55%
“…Clinical remission, a composite outcome defined by a (PRO, patient reported outcome) of resolution of rectal bleeding and near normalisation of stool frequency and endoscopic healing based on MES 0 or 1, is the recommended treatment target in patients with UC, based on recent guidelines 1 . Approximately 50%‐60% patients with EH achieve histologic remission, whereas others have persistent histological activity 2 . Histologic remission, regardless of clinical and endoscopic activity, may have superior long‐term outcomes, 3‐5 warranting its examination as a treatment target in patients with UC 6 .…”
Section: Introductionmentioning
confidence: 99%
“…In clinical practice the finding of Mayo endoscopic subscore (MES) 0–1 is considered “endoscopic remission” [3]. Recent data, however, indicates that MES 1 is not completely normal with regards to inflammatory histological state [6]. This increases the risk of relapse [7] and later complications.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is considered that the association of 5-ASAs with a MES of 0 (the finding that a MES of 0 may be used as an index for the dose reduction of 5-ASAs) is different from the results of the present study. Additionally, while it has been reported that there are differences between MES 0 and MES 1 in terms of remission maintenance rates and surgery rates 2,4042 , we found that it is also important to not only perform an endoscopic mucosal assessment but also to confirm histological healing, in order to ensure remission maintenance 43 . As the research gap in UC treatment, we studied the clinical issue of IM withdrawal was possible or not in UC cases that achieved MH.…”
Section: Discussionmentioning
confidence: 65%